Protective Potential of Maresins in Cardiovascular Diseases - Liu, Min; He, Huixiang; Chen, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases are the leading causes of global mortality. Growing evidence suggests that unresolved inflammation contributes to the chronicity, progression and morbidity of many cardiovascular diseases, thus emphasizing the urgent need to illuminate the mechanisms controlling inflammation and its resolution, for the sake of new effective therapeutic options. Macrophage mediators in resolving inflammation (Maresins) are a family of specialized pro-resolving lipid mediators (SPMs) derived from the ω-3 fatty acid docosahexaenoic acid (DHA). Studies have indicated that Maresins play critical role in initiating the pro-resolving functions of phagocytes, decreasing the magnitude of the overall inflammatory response, and thereby protecting against inflammation-related disorders. In this review, we summarize the detailed actions and the therapeutic potential of Maresins, with a particular emphasis on Maresin-1 (MaR1), in cardiovascular diseases. We hope this review will lead to new avenues to Maresins-based therapies for inflammation-associated cardiovascular diseases.